Green Finance Performance and Role of Sustainability Engineers in the Greater Bay Area. Issue 2 (November 2020) - Lee, Hei Yan; So, Gladys; Tang, Ellie; Lam, Tony; Cheng, Vincent
Abstract: To encourage the implementation of sustainable green features, large scale infrastructure and transportation projects, the Central Government and HKSAR government is keen to promote green finance, determined to develop Hong Kong as the leading hub in the Greater Bay Area region [1]. Since 2016, a series of green finance developments accelerated, including the setting up of Hong Kong Green Finance Association (HKGFA) and the launching of Green Finance Certification Scheme. The green finance development in the Greater Bay Area, in particular Hong Kong, is outlined using a case study of the New World Development Company Limited ("the Group") approach to green financing and their recently completed project – K11 ATELIER King's Road. The paper discusses the role of sustainability engineer in green finance project throughout the four components of green finance project by providing technical support to quantify and assess the environmental impacts and benefits. In particular, sustainability engineers can contribute in green finance by developing a standardized benchmarking system on green building environmental impacts and benefits. The need of benchmarking system is discussed using the first green loan project in Hong Kong, K11 ATERLIER King's Road, as case study. The harmonious collaboration between financial experts and engineering professionals is encouraged in order to push the boundary of sustainability technology. The authors discuss an effective collaboration approach delivered by sustainability engineering professionals to support and create a greater impact of the green finance development in the Greater Bay Area.